NON-VERBAL EQUIVALENTS OF TERMS IN THE FIELD OF ICT - STOFFA, Ján; STOFFOVÁ, Veronika (Trends in education, 2013)
The study points to the fact that in professional communication increasingly parallel to standard or standardized terms their various non-verbal equivalents are used too. It characterizes some frequent types of non-verbal equivalents of terms. It shows that in the field of ICT has emerged and increasingly used some new forms of non-verbal equivalents of terms. It refers to cases where the use of non-verbal equivalents is not appropriate.
Keywords: terms; non-verbal equivalents of terms; acronyms; abbreviations; symbols; pictograms